Justification of Present Status of Green Banking in Bangladesh - Ahsan, Mohammad Kamrul; Uddin, Md. Shamsu (Asian Accounting and Auditing Advancement, 2019)
For climate change and global warming, all the financial institutions in this world, including those of Bangladesh try to adopt the ‘Green’ concept in many ways. Green banking is one of these actions, how bank goes green, collection of all activities related to saving the environment. Traditional banking systems focused on only earning a profit, while green banking systems focused on earning profit and saving the environment. A traditional bank will become a green bank whenever it directs its core operations toward the betterment of the environment. As per the consciousness of green banking practice, Bangladesh Bank (BB) has prepared a Green Banking Policy Guideline in February 2011 to protect against environmental degradation and maintain sustainable banking practices. The aim of this paper is to identify the cause of adopting and present a scenario of green banking practices in Bangladesh. This paper is basically based on secondary data available from related websites, published reports, and articles. This study has shown that only some private and foreign commercial banks have adopted green banking guidelines and financed some green projects. On the other hand, state-owned commercial and specialized development banks have no remarkable initiatives. But, all the green banking activities in Bangladesh are up warding in trends.